(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Corruption in international sports has evolved into a systemic threat that undermines the foundational principles of fair play, integrity, and the "Olympic spirit." This article examines the multifaceted nature of sports corruption, distinguishing between competition-related misconduct (e.g., match-fixing, doping) and institutional management corruption (e.g., bribery in bidding processes, electoral fraud). Through a review of existing literature, this study identifies the mechanisms through which corruption erodes institutional credibility, damages sponsor relations, and distorts the competitive landscape. Finally, the paper suggests that addressing these challenges requires a shift toward more robust governance, enhanced transparency, and structured international oversight.